2023
DOI: 10.1111/jdv.19686
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of mental health comorbidity in patients with atopic dermatitis: An analysis of global trends from 1998 to 2022

Xiao‐ce Cai,
Si‐han Wang,
Chun‐xiao Wang
et al.

Abstract: The prevalence rates of attention deficit hyperactivity disorder (ADHD), depression, anxiety and suicide are increasing in patients with atopic dermatitis (AD), although no research has systematically examined these trends yet. Here, we explore the prevalence of the occurrence of comorbidities, such as ADHD, depression, anxiety and suicide with AD. We searched seven electronic databases from inception to October 2022 to identify relevant studies, and the Agency for Healthcare Research and Quality (AHRQ) and Ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 115 publications
0
1
0
Order By: Relevance
“…Established studies have shown that chronic inflammation of the skin is not only a local problem. It induces inflammation in organs throughout the body, causing cardiovascular and cerebrovascular disorders, systemic amyloidosis, and other organ damage [ 20 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. Furthermore, it is known to induce inflammation in adipose tissue, with known effects such as weight loss due to adipose tissue atrophy, decreased heat production capacity, and increased production of inflammatory adipocytokines [ 23 , 36 , 37 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Established studies have shown that chronic inflammation of the skin is not only a local problem. It induces inflammation in organs throughout the body, causing cardiovascular and cerebrovascular disorders, systemic amyloidosis, and other organ damage [ 20 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. Furthermore, it is known to induce inflammation in adipose tissue, with known effects such as weight loss due to adipose tissue atrophy, decreased heat production capacity, and increased production of inflammatory adipocytokines [ 23 , 36 , 37 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%